Avaliação da implementação da Educação Sexual em contexto escolar, na região do Algarve - A perspetiva de atores educativos responsáveis pela Educação para a Saúde/Educação Sexual - Liliana Paulos; Sandra T. Valadas (Universidade do Minho, 2015)
A case study was performed under the interpretative/qualitative paradigm, with the main objective of evaluating the implementation of Sexual Education (SE) in the Algarve region (Portugal). We interviewed eight Health Education/Sexual Education (HE/SE) coordinators and one director of a cluster of schools (CS). Our results showed that all CS have integrated SE in their educational programs and that CS that are located in areas with fewer residents followed the legal recommendations more strictly. Each CS has designated a specific teacher to coordinate HE/SE and one CS did not have a supporting office. Natural Sciences were identified as the more active subject in SE. The increment and consolitation of knowledge was mostly performed on a preventive approach. The little support from the Ministry of Education and Science and the lack of training and experience, as well as the discomfort of teachers were identified as constraints in the implementation of the SE process.